Profile of Higher Order Thinking Skills (HOTS) of Class IV Students on Energy Resources at Ma'arif Sentul: Profil Higher Order Thinking Skills (HOTS) Siswa Kelas IV Pada Materi Sumber Energi di Ma’arif Sentul - Rohmah, Ayu Ashimatur; Wulandari, Fitria Eka (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this study is to describe the Higher order thinking skill (HOTS) profile of fourth grade students on the Energy Sources Material at MI Ma'arif Sentul. The research method used in this research is a survey type research method, the population used is all students of MI Ma'arif Sentul, with a sample of 23 students taken randomly who obtained from calculations using the Slovin formula. The data collection technique used is the test. The research instrument used was a matter of high-order thinking skills. The test results were then analyzed using the high-order thinking skills formula (HOTS) and described into 3 criteria, namely analyzing, evaluating, and creating. Based at the outcomes of the analysis, it may be concluded that student at MI Ma'arif Sentul have high-order thinking skills (HOTS) at a good level in the material source of energy.